2008
DOI: 10.1113/jphysiol.2008.153791
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring changes in membrane phosphatidylinositol 4,5‐bisphosphate in living cells using a domain from the transcription factor tubby

Abstract: Phosphatidylinositol 4,5-bisphosphate (PtdIns(4,5)P 2 ) is a key component in signal transduction, being a precursor to other signalling molecules and itself associated with roles in signal transduction and cell biology. Tubby is a membrane bound transcription factor whose dysfunction results in obesity in mice. It contains a domain that selectively binds PtdIns(4,5)P 2 . We have investigated the use of a fluorescently tagged version of this domain to monitor changes in PtdIns(4,5)P 2 concentration in living c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
110
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(120 citation statements)
references
References 44 publications
10
110
0
Order By: Relevance
“…To study roles of key signaling lipids, PtdIns(4,5)P 2 , and PtdIns(3,4,5)P 3 in the regulation of cellular proteins in a simple, comprehensive, and explicit manner, we generated a library of distinct LBDs obtained from diverse cellular proteins and determined their subcellular localization. Our study showed that most FYVE and PX domains are endosome-localized, whereas ENTH and Tubby domains are PM-associated, as expected from their reported lipid specificity (42)(43)(44). The study also revealed that the FYVE domain of protrudin is localized to PM and the nucleus instead of endosomes, unlike typical FYVE domains (45).…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…To study roles of key signaling lipids, PtdIns(4,5)P 2 , and PtdIns(3,4,5)P 3 in the regulation of cellular proteins in a simple, comprehensive, and explicit manner, we generated a library of distinct LBDs obtained from diverse cellular proteins and determined their subcellular localization. Our study showed that most FYVE and PX domains are endosome-localized, whereas ENTH and Tubby domains are PM-associated, as expected from their reported lipid specificity (42)(43)(44). The study also revealed that the FYVE domain of protrudin is localized to PM and the nucleus instead of endosomes, unlike typical FYVE domains (45).…”
Section: Discussionsupporting
confidence: 46%
“…1, C and D), five of them belonged to the ENTH and Tubby domains (Fig. 1, C and E), which are known to interact with PtdIns(4,5)P 2 (42)(43)(44). Intriguingly, the other PM-localized LBD was the FYVE domain of protrudin (Fig.…”
Section: Identification Of Pm-localized Lbds-mentioning
confidence: 99%
“…Mouse type I PIP5Ks cloned into pcDNA3-Myc vector were used as DNA templates for quantitative real time PCR (qRT-PCR) analysis. The YFP-tagged tubby mutant (R332H) was provided by Andrew Tinker (University College London, UK) (38), and TIRAP-GFP and HA-TIRAP were gifts from Ruslan Medzhitov (Yale University). PCR-amplified inserts of Tubby or TIRAP were subcloned into the EcoRI-XhoI sites of the mRFP-pcDNA3 vector to generate mRFP-Tubby-R332H and mRFP-TIRAP.…”
Section: Methodsmentioning
confidence: 99%
“…Imaging experiments (Figure 1) also suggest that despite activation of PLC by B 2 R, the overall membrane PIP 2 level in most DRG neurons may not change dramatically, since YFP-tubby (PIP 2 reporter that does not bind IP 3 ; ref. 19) did not translocate in response to BK application (until B 2 Rs were overexpressed).…”
Section: Discussionmentioning
confidence: 99%
“…However, since PLCδ-PH-GFP has a higher affinity for IP 3 than for PIP 2 , translocation of the probe does not necessarily indicate a significant drop in membrane PIP 2 levels, as even small amounts of hydrolyzed PIP 2 may produce enough IP 3 to cause the probe to translocate (13,18). Thus, we used a new PIP 2 probe (YFP-tubby, R332H mutated), which does not bind IP 3 (19), to probe whether there was a significant depletion of the membrane PIP 2 pool. Like PLCδ-PH-GFP, the YFP-tubby also localized predominantly to the plasma membrane ( Figure 1B); however, unlike PLCδ-PH-GFP, YFP-tubby failed to translocate to the cytosol after BK application in 11 of 12 neurons tested (see also Supplemental Figure 2).…”
Section: Introductionmentioning
confidence: 99%